Dynamic inter-fibre failure of unidirectional composite laminates with through-thickness reinforcement - Cui, Hao; Yasaee, Mehdi; Melro, António R. (Elsevier, 2019)
Unidirectional composite laminates reinforced in the thickness direction with Z-pins are tested in tension and compression with different off-axis angles at high loading rate. A split Hopkinson bar setup and a high speed imaging system have been used for these dynamic tests. It is found that the inter-fibre strength was reduced by Z-pinning in tension and shear dominated failure modes, and the reduction from dynamic loading conditions is greater than that in quasi-static. However, the laminate strength was not significantly influenced by Z-pinning when loaded predominantly in compression. This difference was caused by the transition of failure mechanisms around Z-pins. The stiffness of the laminate was not affected by Z-pins at elevated strain rates, since the increased epoxy stiffness helped to make up for the stiffness loss due to reduced fibre volume fraction resulting from Z-pins.